2008
DOI: 10.1016/j.crvi.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new molecules extracted from Quercus suber L. cork

Abstract: Various methods of suberin extraction have been used in order to identify monomers of this complex polymer. Pre-extraction of waxes has allowed us to identify for the first time 3-friedelanol as a terpen from cork. Moreover, the wax chemical composition found here varied from previous results since cerin was not identified while friedelin and betulin were. Three fractions were obtained: a polymeric, a monomeric and a low molecular weight fraction, the last of which has never before been described. 2,6-heptaned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
0
19
1
1
Order By: Relevance
“…[40] A cork suberin hydrolysate was shown to act as an J. Graça, S. Santos anti-ageing agent with smoothing anti-wrinkle action in human skin. [41] Promising results were obtained in the synthesis of polyurethane foams, after the oxypropylation of cork suberin. [42,43] Important amounts of plant wastes rich in suberin are available each year.…”
Section: Suberin Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] A cork suberin hydrolysate was shown to act as an J. Graça, S. Santos anti-ageing agent with smoothing anti-wrinkle action in human skin. [41] Promising results were obtained in the synthesis of polyurethane foams, after the oxypropylation of cork suberin. [42,43] Important amounts of plant wastes rich in suberin are available each year.…”
Section: Suberin Applicationsmentioning
confidence: 99%
“…Suberin was found to inhibit mutagenesis39 and to work as an absorbent of carcinogens 40. A cork suberin hydrolysate was shown to act as an anti‐ageing agent with smoothing anti‐wrinkle action in human skin 41. Promising results were obtained in the synthesis of polyurethane foams, after the oxypropylation of cork suberin 42,43…”
Section: Suberin Applicationsmentioning
confidence: 99%
“…Jellemző a kéregre a parásodáshoz nélkülözhetetlen szuberin jelenléte is (Cordeiro et al 1998, Gandini et al 2006, Graça & Santos 2006, Coquet et al 2008, Jové et al 2011, Miranda et al 2012, 2013. Jové et al (2011) Quercus suber kérgét vizsgálták: szuberin és lignin volt a két legnagyobb mennyiségben előforduló anyag.…”
Section: Szervesanyag öSszetételunclassified
“…Suberin is essential to suberification (Cordeiro et al 1998;Gandini et al 2006;Jové et al 2011;Sudakova et al 2012;Miranda et al 2013). Coquet et al (2008) tried to identify suberin monomers, finding 3-friedelanol, 2,6-heptanediol, friedelin, and betulin. Graça andSantos (2006a, 2006b) concluded that cork suberin is a glycerol-containing lipid, the main monomers are glycerol, long-chain α,ω-diacids and ω-hydroxyacids, and the molecule size of the suberin is similar to other biopolymers.…”
Section: Organic Compoundsmentioning
confidence: 99%